Relationship between Parental Concerns about Social-Emotional Reciprocity Deficits and Their Children's Final ASD Diagnosis - Ronit Saban-Bezalel; Einat Avni; Esther Ben-Itzchak; Ditza A. Zachor (MDPI AG, 2023)
Concerns raised by parents regarding their child's development are compatible with the child's final diagnosis of autism spectrum disorder. A better understanding of the relationship between parental concerns and a final diagnosis of autism spectrum disorder is therefore critical. In the current study, we compared the frequencies of parental concerns related to DSM-5 criteria for autism spectrum disorder between pair-matched groups with and without a final diagnosis of autism spectrum disorder and determined which parental concerns predicted a final diagnosis of autism spectrum disorder. The cohort included 80 participants (48-154 months of age, IQ > 70) assessed for a possible autism spectrum disorder diagnosis. Parental concerns were retrieved from the free-description portion of the introductory questions of the Autism Diagnostic Interview-Revised and analyzed to assess whether they corresponded to any of the seven DSM-5 criteria for ASD. The two groups only differed in the frequency of parental concerns relating to deficits in social-emotional reciprocity. Parents of children diagnosed with autism spectrum disorder were four times as likely to report deficits in social-emotional reciprocity. This finding highlights the significance of parental concerns regarding deficits in social-emotional reciprocity in predicting a final diagnosis of autism spectrum disorder.